Development of a Geometric Transformation Pop-Up Book to Improve Students’ Problem-Solving Skills - Fitriana, Laila; Munawaroh, Fathul (FKIP Universitas Lampung, 2025)
Problem-solving skills are crucial in mathematics education as they are one of the mathematics learning objectives. However, based on PISA results, students' problem-solving skills in Indonesia are still low, necessitating efforts to address this issue. Based on this problem, this study aims to develop a valid, practical, and effective pop-up book learning media to improve problem-solving skills in geometry transformation materials. This developmental study used the ADDIE development model, which consisted of analysis, design, development, implementation, and evaluation. This research employed a quasi-experimental design using two classes with similar problem-solving abilities as the experimental and control classes, as demonstrated by an average balance test on pretest scores. Each class contains 31 students. Learning media is considered valid and practical if its validity and practicality scores are 61% or higher. Learning media is deemed effective if it can improve students' problem-solving skills, as evidenced by a t-test on the students' post-test scores. The research results show that the pop-up book learning media is very valid, with an average score of 81.25% from material experts and 83.33% from media experts. The pop-up book media is considered very practical based on the teacher's response score of 83.33% and students' response score of 84.11%. Additionally, the experimental class in this study showed a statistically significant improvement with a p-value of 0.004 (less than 0.05) compared to the control class; thus, the pop-up book learning media can be declared effective in improving students' problem-solving skills. Therefore, it can be concluded that the pop-up book learning media is very valid, practical, and effective in enhancing students' problem-solving abilities in geometric transformation. Keywords: pop-up book, learning media, problem-solving skills.